Comparison of 4 sinus augmentation techniques for implant placement with residual alveolar bone height ⩽3 mm. Issue 46 (13th November 2020) - Tsai, Chia-Fang; Pan, Whei-Lin; Pan, Yi-Ping; Chan, Chiu-Po; Ju, Yuh-Ren; Wang, Yuan-Min; Lin, Cho-Ying; Chang, Chi-Ching
Abstract : Abstract: This study compared implant outcomes following maxillary sinus floor augmentation (MSFA) in edentulous patients with a residual alveolar bone height ⩽3 mm. Four techniques were evaluated: 1-stage bone-added osteotome sinus floor elevation procedure (BAOSFE) with simultaneous implant placement; 2-stage BAOSFE with delayed implant placement; 1-stage lateral window sinus floor elevation with simultaneous implant placement; and 2-stage lateral window sinus floor elevation with delayed implant placement. Patients were followed for 18 to 72 months (mean: 52.5 months) after prosthesis placement. Data were analyzed with cone-beam computed tomography. A total of 96 implants from 71 patients were analyzed; pretreatment, there were no significant differences between patients. Total implant survival was 98.9%. The mean residual bone height was significantly higher in the 1-stage BAOSFE group than the other groups ( P  < .01); 1 implant in this group failed at 3 months. There was no significant difference in total bone height gain between groups. However, the bone height gain of 1st sinus lifting with 2-stage BAOSFE was significantly lower than the 2-stage lateral window procedure ( P  < .01). There was no prosthesis failure. The favorable implant outcomes suggest these 1-stage and 2-stage MSFA procedures should be considered as alternative treatment options for patients with extremely atrophic posterior maxilla.